(untitled) (Research, Society and Development, 2020)
The “Serra da Ibiapaba” is an agricultural center of major importance for the Ceará State, generating employment and income for the entire Northeastern region of the Brazil. However, the countries of this region face difficulties in maintaining their productive areas. Among the most limiting factors of production, is the pests when above the level of economic damage cause occasional losses of up to 100% of production. This paper aimed to characterize the use and knowledge of the principles of Integrated Pest Management among the producers of “Serra da Ibiapaba”. Thus, a questionnaire with 39 questions was applied to 25 producers from different municipalities in the region. It was verified that the IPM is not yet part of the reality of the producers, those who carry out the pest control, almost the exclusion, the use of pesticides, the high frequency of spraying and in high dosages. Biological control, as well as other tools of a more conservationist nature, are more used by this group of producers, which is mainly due to the lack of knowledge and technical training, reflecting the absence of technical assistance.